The pro-inflammatory cytokine Tumor Necrosis Factor alpha (TNF-α) in Diabetic Nephropathy - Alia KH Mahmoud; Muhammed Ahmed Abd El Moety; Amal Khalifa Ahmed; Samer A. El-Sawy (SVU - International Journal of Medical Sciences)
Background: Diabetic nephropathy has become the main cause of renal failure, and furthermore, is associated with a dramatic increase in cardiovascular risk. Regretfully, we still don't fully understand the mechanisms underlying the onset and progression of renal injury in diabetes. There is now proof that inflammation and activated innate immunity play important roles in the etiology of problems with diabetes. Furthermore, a variety of inflammatory chemicals, including pro-inflammatory cytokines like tumor necrosis factor-alpha (TNF-α). Objectives: is to detect the role of TNF-α as a pathogenic factor in diabetic nephropathy. Patients and methods:: Between January 2022 and June 2022, 50 diabetic study participants sought medical care at the Sohag University Hospital's outpatient diabetes clinic. They were compared to 25 people who appeared to be in good condition. TNF-α level in the serum was measured in 25 individuals with diabetes, 25 individuals with diabetic nephropathy, and 25 healthy controls by enzyme-linked immun-osorbent assay (ELISA). Results: As compared to healthy controls, the diabetes and DN groups had significantly higher serum levels of TNF-α. TheTNF-α level and the duration of diabetes have a significant (positive) association, (P<0.05), a strong (positive) correlation (P<0.05) between TNF-α and the albumin creatinine ratio. A moderately positive correlation was seen between TNF-α and HBA1C and demonstrating a significant inverse relationship (P<0.05) between TNF-α and eGFR. Conclusion: Our results indicated that serum levels of TNFα were significantly higher in diabetics and diabetic nephropathy group compared to the control group.